Peran Mediasi Creative Self-Efficacy Dan Knowledge Sharing Pada Pengaruh Entrepreneurial Leadership Terhadap Innovative Work Behavior Karyawan R&D Industri Food & Baverage Di Kota Malang - Tri Setyo Prasojo, Rosana; Rizki Sridadi, Ahmad (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2025)
This study aims to examine the influence of entrepreneurial leadership on the innovative work behavior of R&D employees in the food and beverage industry in Malang City, by identifying the mediating roles of creative self-efficacy and knowledge sharing. This research is motivated by the phenomenon of rapid growth in the food and beverage industry in Malang, which is increasingly crowded but tends to be dominated by copycat practices with a lack of genuine innovation. In this context, entrepreneurial leadership plays a crucial role in fostering innovative work behavior needed to build competitive advantage. The study employs a quantitative approach using Partial Least Square-Structural Equation Modeling (PLS-SEM) for data analysis. A total of 201 respondents, who are R&D employees from various food and beverage companies in Malang City, were selected through purposive sampling. The results indicate that entrepreneurial leadership has a positive and significant effect on creative self-efficacy, knowledge sharing, and innovative work behavior. Furthermore, both creative self-efficacy and knowledge sharing also significantly influence innovative work behavior. These findings suggest that the two variables partially mediate the relationship between entrepreneurial leadership and innovative work behavior. This study contributes theoretically to the development of the Componential Theory of Creativity and offers practical implications for companies to foster an innovative culture in R&D environments through entrepreneurial leadership and knowledge collaboration.